Cardiovascular events after discontinuation of low-dose aspirin - Pareek, Manan; Kristensen, Steen D.; Grove, Erik L. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Fueled by the massive ~50% relative risk reduction of death or myocardial infarction demonstrated in early randomized, controlled trials of patients with acute coronary syndromes, aspirin has played a pivotal role in treatment and prevention of cardiovascular disease for more than 30 years (1,2).